Actitudes de los docentes frente a la inclusión educativa de estudiantes con trastornos depresivos - Bejarano, Jessica; Narváez, Gabriela (Revista Ecos de la Academia, 2021)
Abstract The attitude of teachers in the educational inclusion process is a key factor that can have a positive or negative impact on students with depressive disorders. Students with depression are a vulnerable group within educational institutions because it is one of the most common psychological disorders. The aim of the study was to analyze the attitudes of teachers towards the educational inclusion of an adolescent with a depressive disorder. The methodology used was qualitative, with a case study design. The results revealed that teachers have an indifferent attitude towards the inclusion of students with depression, even though they agree with the idea that inclusion is a benefit for all students with Special Educational Needs. Finally, an awareness plan was proposed to teachers about depressive disorder and the educational inclusion of students with this condition.